2022
DOI: 10.3389/fphys.2022.1035538
|View full text |Cite
|
Sign up to set email alerts
|

Connecting gut microbiomes and short chain fatty acids with the serotonergic system and behavior in Gallus gallus and other avian species

Abstract: The chicken gastrointestinal tract has a diverse microbial community. There is increasing evidence for how this gut microbiome affects specific molecular pathways and the overall physiology, nervous system and behavior of the chicken host organism due to a growing number of studies investigating conditions such as host diet, antibiotics, probiotics, and germ-free and germ-reduced models. Systems-level investigations have revealed a network of microbiome-related interactions between the gut and state of health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 223 publications
0
4
0
Order By: Relevance
“…Officially, FFAR2 appears to be the only reported FFAR gene in the chicken genome, while many mammal genomes have four identified FFAR genes [ 71 , 72 ]. However, some studies have evaluated the expression of other putative FFAR genes in chickens and found them to be associated with oral and intestinal nutrient sensing; serotonin expression and behavior; PPAR-related gluconeogenesis; and immune cell regulation [ 73 , 74 , 75 , 76 ]. In mammals, the different FFAR genes have an affinity for FA of different lengths.…”
Section: Effects On Intestinal Morphology Gut Immunity and The Microb...mentioning
confidence: 99%
“…Officially, FFAR2 appears to be the only reported FFAR gene in the chicken genome, while many mammal genomes have four identified FFAR genes [ 71 , 72 ]. However, some studies have evaluated the expression of other putative FFAR genes in chickens and found them to be associated with oral and intestinal nutrient sensing; serotonin expression and behavior; PPAR-related gluconeogenesis; and immune cell regulation [ 73 , 74 , 75 , 76 ]. In mammals, the different FFAR genes have an affinity for FA of different lengths.…”
Section: Effects On Intestinal Morphology Gut Immunity and The Microb...mentioning
confidence: 99%
“…Line 7 2 chickens have lower levels of brain serotonin (5-HT) than line 6 3 chickens. Serotonin dysregulation has been implicated in a range of neuropsychiatric disorders in humans and various animals including chickens [ 118 , 119 ]. Lower levels of 5-HT have also been found in the brain of violent offenders [ 120 , 121 , 122 ].…”
Section: Genetic Lines and Study Designmentioning
confidence: 99%
“…Accumulating studies from various animal models in gut microbiota investigations, such as GF (complete absence of microbial exposure) animals, SPF (specific pathogen-free) animals, antibiotic-treated (broad-spectrum antibiotic cocktails) animals, and animals exposed to pathogenic bacterial infections, suggest that the gut microbiota plays an important role in the regulation of anxiety, mood, and cognition, indicating the possibility of using probiotics to modify the gut microbiota to control impulsive and compulsive behaviors in patients with neuropsychiatric disorders [ 158 , 159 , 160 , 161 ]. Like mammals, the gut microbiome plays a critical role in poultry health and welfare [ 119 , 162 , 163 ]. Laying hens showing high or low FP have different gut microbial populations [ 27 , 94 , 95 , 164 ] and metabolite profiles [ 96 , 97 ].…”
Section: Cecal Microbiota Transplantation Social Stress and Injurious...mentioning
confidence: 99%
“…These studies re ect the key interactions between neural factors, the gut microbiome, and GALT physiology. In avian species, there is emerging evidence of the gut-brain crosstalk [27][28][29] suggesting similar mechanisms as in mammalian models.…”
Section: Introductionmentioning
confidence: 99%